2012
DOI: 10.1016/j.ypmed.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Money as motivation to quit: A survey of a non-random Australian sample of socially disadvantaged smokers' views of the acceptability of cash incentives

Abstract: Given high smoking prevalence among socially disadvantaged groups and consequent health disparities, it is imperative novel methods of encouraging smoking cessation are explored and tested. This survey found financial incentives may be an acceptable method. Further research to understand all possible positive and negative effects is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
2
10
0
1
Order By: Relevance
“…This is one of only a few qualitative studies on acceptability of HPFI [ 19 , 20 , 22 , 27 , 30 , 33 , 45 - 48 , 62 - 66 ] and one of only a limited number of empirical research studies on this topic including UK participants. In a cross-section of the public we found a range of views on the acceptability of HPFI which mostly reflected the themes we developed in a systematic review on this topic [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is one of only a few qualitative studies on acceptability of HPFI [ 19 , 20 , 22 , 27 , 30 , 33 , 45 - 48 , 62 - 66 ] and one of only a limited number of empirical research studies on this topic including UK participants. In a cross-section of the public we found a range of views on the acceptability of HPFI which mostly reflected the themes we developed in a systematic review on this topic [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those that have been conducted were restricted to alcohol, drug, and smoking cessation practitioners, managers and service providers, [ 21 , 20 ] pregnant women [ 26 ] and Maori, Pacific Islanders and low income groups [ 27 ]. Thus, growing, but still limited qualitative research on acceptability of HPFI has been conducted with a cross-section of participants, with limited research having been carried out in the United Kingdom (UK) [ 19 , 27 , 30 , 45 - 48 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the financial benefits of smoking cessation among those experiencing hardship, public health efforts have emphasized the money that can be saved by households when quitting smoking (13) and many tobacco control programs have even offered financial incentives for quit efforts (1417). However, research has shown that an interest in quitting does not always translate into actual quit attempts or smoking abstinence (12).…”
Section: Introductionmentioning
confidence: 99%
“…En relación con este último aspecto, es importante seña-lar el posible impacto que generan los incrementos en los impuestos en la conducta de los fumadores, es decir, no sólo en la incidencia en la reducción del consumo sino también en la cesación y la disposición al pago. 22 También existen otros aspectos importantes en relación con la percepción de los fumadores y su altruismo respecto del daño del humo a terceros, y que de igual manera interactúa en su conducta respecto de los riesgos de fumar. De acuerdo con la EMTA, 41% de los fumadores que han visto las advertencias sanitarias pensaron en dejar de fumar (47.7% mujeres y 39% hombres).…”
Section: Discussionunclassified